Falzifikace a disneylandizace města - Cílek, Václav (Lidé města, 2005)
The changes of the historical centres of some most important Czech towns (Praha, Český Krumlov) were after 1990 abrupt and for residents often extremely demanding and unpleasant ones. Almost 4000 residents have left the Prague historical city centre (total population is now aprox. 16 thousand residents). Unlike in 60ties and 70ties when most of the visitors were coming for a personal education, the entertainment seems now to be the principal motive for the majority of tourists. Example of this trend can be viewed e.g. by establishing of a new kind of museum – museums of tortures, that seem to fill the demand for “big emotions“ of emptified mass tourism. The loss of a distinct “genius loci“ is the result of entertainment consumption – towns like Madrid, Praha, Madrid seems now to in respect to emotional atmosphere to be amost replaceable cities. The remedy might be simple and traditional one – to keep residents and functioning social network in the historical city centres.